2014
DOI: 10.1177/1721727x1401200214
|View full text |Cite
|
Sign up to set email alerts
|

The Peripheral Network between Oxidative Stress and Inflammation in Multiple Sclerosis

Abstract: M.R. and R.E contributed equally to this workReactive oxygen species(ROS) are mainly produced by microglia and macrophages during inflammationdriven oxidative burst. However, they can in turn affect the reactivity and function ofimmune cells.For the first time, the relationship between these two key players involved in Multiple Sclerosis (MS) was evaluated at peripheral level. We performed an in-depth immune-phenotypic and functional analysis ofMBP (Myelin Basic Protein)-stimulated Peripheral Blood Mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have shown that neuroinflammation and oxidative stress are concurrently involved in the pathogenesis of MS. Noticeably, oxidative stress plays a pivotal role in the initiation and progression of MS [ 90 , 117 ].…”
Section: Role Of Ros In the Mechanisms Of Ms Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that neuroinflammation and oxidative stress are concurrently involved in the pathogenesis of MS. Noticeably, oxidative stress plays a pivotal role in the initiation and progression of MS [ 90 , 117 ].…”
Section: Role Of Ros In the Mechanisms Of Ms Pathogenesismentioning
confidence: 99%
“…One of the factors that may regulate the pathogenesis of MS is endogenous antioxidant enzyme systems. Several reports have highlighted the increased expression of antioxidant enzymes, such as SOD1 and SOD2, and catalase in actively demyelinating MS lesions; hence, increased expression of antioxidant enzymes in inflammatory MS lesions is associated with neuroinflammation [ 117 , 128 ]. The inflammation and cell death in the brain could be regulated by Nrf2.…”
Section: Antioxidant Systems and Multiple Sclerosismentioning
confidence: 99%
“…Mast cells stimulate activated T cells, and this effect is further increased when MCs are activated by myelin and is in part dependent on TNF alpha. MS is a predominantly Th l-cell-mediated disease, therefore, it appears that inflammatory response in MS patients (27) involve cytokine release and MC mediators, including other inflammatory cells such as macrophages and lymphocytes. Although mast cell-mediated demyelination is largely assumed to be a T-cell-dependent process, driven by a myelinspecific auto-antigen (l).…”
mentioning
confidence: 99%
“…Human MCs release matrix metalloproteinase-9 and IL-6 in response to activated T cells, and myelin, which is partially regulated by TNF α , stimulates MCs in a way that increases the number of activated T cells. MS [ 278 ], a Th1-cell-mediated illness, displays an inflammatory response that includes the production of cytokines and MC mediators in addition to other inflammatory cells like lymphocytes and macrophages. Though it is widely acknowledged that MC-mediated demyelination, which is brought on by an auto-antigen specific to myelin, requires T-cells [ 279 ].…”
Section: Mast Cellsmentioning
confidence: 99%